Transformasi Digital dalam Dakwah: Inovasi Masjid PUSDAI Jawa Barat dalam Mengintegrasikan Teknologi Informasi: Digital Transformation in Da'wah: Innovation of the West Java PUSDAI Mosque in Integrating Information Technology - Rachmawaty, Silvia Siti; Fakhruddin, Agus; Rizal Permana (QULUBANA: Jurnal Manajemen Dakwah, 2024)
Digital transformation compels continuous adaptation to rapid technological advancements to survive in a competitive environment. The integration of information technology has become a strategic step in enhancing the effectiveness of religious outreach. This research aims to examine digital transformation in religious outreach at Pusdai Mosque in Bandung, focusing on the integration of information technology, such as websites and social media, to understand how this technology is used to expand the reach of religious messages and improve interaction with the congregation. The method used is qualitative with a phenomenological approach, involving in-depth interviews with operational managers, mosque administrators, and active congregation members, as well as direct observation during religious activities and analysis of documents and social media from Pusdai itself. The results of the study indicate that the integration of information technology at Pusdai Mosque in Bandung has successfully increased the effectiveness of religious outreach and congregation participation. However, significant challenges related to human resources and funding remain. The strategies employed to address these challenges include internal training, internship programs, and external collaborations. This study offers recommendations to the public on how mosques can leverage information technology to support religious outreach in the digital era.